Characterization of Helianthus annuus Lipoic Acid Biosynthesis: The Mitochondrial Octanoyltransferase and Lipoyl Synthase Enzyme System - Martins-Noguerol, Raquel; Acket, Sébastien; Troncoso-Ponce, M. Adrián; Garcés, Rafael; Thomasset, Brigitte; Venegas-Calerón, Mónica; Salas, Joaquín J.; Martínez-Force, Enrique; Moreno-Pérez, Antonio J. (Frontiers in Plant Science, 2021)
Lipoic acid (LA, 6,8-dithiooctanoic acid) is a sulfur containing coenzyme essential for the activity of several key enzymes involved in oxidative and single carbon metabolism in most bacteria and eukaryotes. LA is synthetized by the concerted activity of the octanoyltransferase (LIP2, EC 2.3.1.181) and lipoyl synthase (LIP1, EC 2.8.1.8) enzymes. In plants, pyruvate dehydrogenase (PDH), 2-oxoglutarate dehydrogenase or glycine decarboxylase are essential complexes that need to be lipoylated. These lipoylated enzymes and complexes are located in the mitochondria, while PDH is also present in plastids where it provides acetyl-CoA for de novo fatty acid biosynthesis. As such, lipoylation of PDH could regulate fatty acid synthesis in both these organelles. In the present work, the sunflower LIP1 and LIP2 genes (HaLIP1m and HaLIP2m) were isolated sequenced, cloned and characterized, evaluating their putative mitochondrial location. The expression of these genes was studied in different tissues and protein docking was modelled. The genes were also expressed in Escherichia coli and Arabidopsis thaliana, where their impact on fatty acid and glycerolipid composition was assessed. Lipidomic studies in Arabidopsis revealed lipid remodeling in lines overexpressing these enzymes and the involvement of both sunflower proteins in the phenotypes observed is discussed in the light of the results obtained.